Nilai- Nilai Pendidikan Karakter dalam Novel Layangan Putus Karya Mommy ASF - Najla Wani; Hasanah Hasanah (Jurnal Pendidikan dan Konseling (JPDK), 2022)
Capacity and character development are one of the goals of national education in the context of educating the life of the nation. Character development can be done is by developing one's individual character. In the novel Layangan Disconnect by Mommy ASF, there are many lessons that we can take as character education values ??for each reader. This research aims to find out the values ??of character education contained in the Layangan Putus novel. This study uses a qualitative approach to the type of library research (library research). Data collection uses the documentation method through primary and secondary data collection by reviewing novels and finding solutions to research problems from several related books and journals. Research data analysis techniques using content analysis. The results of this study indicate that in the novel Layangan Putus Karya Mommy ASF, which is about infidelity, there are also character values ??that we can apply in our daily life. The educational values ??are mutual cooperation, religious, integrity, independence, and nationalism.